2004
DOI: 10.1080/10401230490453743
|View full text |Cite
|
Sign up to set email alerts
|

Modafinil: Preclinical, Clinical, and Post-Marketing Surveillance—A Review of Abuse Liability Issues

Abstract: Modafinil is an agent that is frequently used in the treatment of narcolepsy. More recently it has been used in the treatment of a variety of psychiatric, neurological, and medical illnesses. Due to its ability to improve wakefulness, modafinil has been viewed as a stimulant. Based on the potential for modafinil to become widely used in a variety of syndromes and settings, evidence from preclinical in vitro and in vivo studies, human laboratory studies, and post-marketing experiences examining the potential ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(119 citation statements)
references
References 38 publications
4
112
0
3
Order By: Relevance
“…Unlike data from our previous study with methamphetamine, ratings of 'good drug effect' and participants' reported desire to take the drug again were not significantly altered by modafinil. This is consistent with clinical observations (for a review, see Myrick et al, 2004) and human laboratory data (Rush et al, 2002), indicating that the abuse potential of modafinil is low.…”
Section: Discussionsupporting
confidence: 77%
“…Unlike data from our previous study with methamphetamine, ratings of 'good drug effect' and participants' reported desire to take the drug again were not significantly altered by modafinil. This is consistent with clinical observations (for a review, see Myrick et al, 2004) and human laboratory data (Rush et al, 2002), indicating that the abuse potential of modafinil is low.…”
Section: Discussionsupporting
confidence: 77%
“…Modafinil was originally developed as a treatment for narcolepsy, and can be used to reduce performance decrements due to sleep loss with apparently small side effects and little risk of dependency (Teitelman 2001;Myrick et al 2004). The drug improved attention and working memory in sleep-deprived physicians (Gill et al 2006) and aviators (Caldwell et al 2000).…”
Section: Drugsmentioning
confidence: 99%
“…In terms of abuse liability, human volunteers selfadminister modafinil more than placebo under certain conditions , but most studies suggest that the medication has low abuse liability even among drug abusers (Jasinski 2000;Rush et al 2002a, b), and post-marketing surveillance indicate modafinil misuse is low (see Myrick et al 2004). The presence of positive mood effects, in fact, is likely a positive feature in that it improves medication compliance.…”
Section: Clinical Datamentioning
confidence: 99%